Bioinspired chemistry for energy : a workshop summary to the Chemical Sciences Roundtable - Schwartz, Sandi; Masciangioli, Tina M. (Tina Marie), 1969-; Boonyaratanakornkit, Boonchai (Online access: NCBI NCBI Bookshelf., 2008)
Faced with the steady rise in energy costs, dwindling fossil fuel supplies, and the need to maintain a healthy environment - exploration of alternative energy sources is essential for meeting energy needs. Biological systems employ a variety of efficient ways to collect, store, use, and produce energy. By understanding the basic processes of biological models, scientists may be able to create systems that mimic biomolecules and produce energy in an efficient and cost effective manner. On May 14-15, 2007 a group of chemists, chemical engineers, and others from academia, government, and industry participated in a workshop sponsored by the Chemical Sciences Roundtable to explore how bioinspired chemistry can help solve some of the important energy issues the world faces today. The workshop featured presentations and discussions on the current energy challenges and how to address them, with emphasis on both the fundamental aspects and the robust implementation of bioinspired chemistry for energy.